Against constitutionalism - Loughlin, Martin (Harvard University Press, 2022)
"Tracing constitutional thought from the Enlightenment to the present, Martin Loughlin shows how a tool for the protection of self-government has become a means for subverting popular will. Across the globe, constitutions now displace democratic decision-making, as courts interpret values in the law that ultimately trump legislative action"--